Econometric Analysis of the Effect of Energy Prices on Exchange Rates During War Period - Afaq Aslanova; Simuzar Mammadova (International Journal of Energy Economics and Policy, 2023)
Petroleum and natural gas, which are among the most used energy sources in the world, have a significant impact on financial markets and macroeconomic indicators as they are used as raw materials in many fields. For this reason, Russia, Turkey, Brazil, and India, as energy importers and developing countries, may be affected positively or negatively by changes in energy prices. The main purpose of this research is to investigate the relationship between the exchange rates of Brent oil, crude oil (WTI), natural gas, the US dollar index, and the Russian ruble. In the study, weekly data between February 6, 2022, and December 25, 2022 were examined. A vector autoregressive model (VAR) was used to examine the relationship between the variables included in the analysis, and the direction of the relationship between the variables was determined by the Granger causality test. According to the results of the VAR model, the WTI price has a significant effect on the USD/RUB rate, but the USD/RUB rate does not have a significant effect on the Brent and crude oil prices. On the other hand, the results of the Granger causality test confirm the findings of the VAR analysis.